The Effect of a Mixture of Biological Fertilizer on Nitrate Increase in Peat Water Media - Abner Arie Pranata Novemberian Marpaung; Syafriadiman Syafriadiman; Saberina Hasibuan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis research was conducted from October to November 2019 at the peatland of Kualu Nenas Village, Tambang District, Kampar District, Riau Province. The purpose of this research is to get a comparsion of the mixture between human waste biofertilizer and cow manure biofertilizer for increased nitrate. The method used in this study was the experimental method of using the Complete Random Draft (CRD) (sudjana, 1991) 1 factor with 6 treatment levels and 3 times repeated. The treatment used is P0 (without biological fertilizers), P1 (provision of biological fertilizer 100%), P2 (provision of biofertilizer mixture 25% human waste : 75% cow manure biofertilizer), P3 (provision of biofertilizer mixture 50% human waste : 50% cow manure biofertilizer), P4 (provision of biofertilizer mixture 75% human waste : 25% cow manure biofertilizer), P5 (the provision of biofertilizer 100% human waste). The study was conducted for 28 days, using a dose 750 gram/m2. The results of this study showed a mixture of biofertilizer 75% human waste : 25% cow manure biofertilizer provides the best solution for a nitrate that is soil nitrate at 2,24-7,67 and water nitrate at 1,41-4,75 with a peak increase in the day 14.Keywords: Peat Soil, Formulation Biofertilizer, Nitrate